2021
DOI: 10.3390/ani11102776
|View full text |Cite
|
Sign up to set email alerts
|

Free Faecal Water: Analysis of Horse Faecal Microbiota and the Impact of Faecal Microbial Transplantation on Symptom Severity

Abstract: Free faecal water (FFW) in equines results in pollution of the hindquarters and tail and can also involve clinical signs. Though the cause of FFW is unknown, it was hypothesized that it may involve the gut microbiota. This hypothesis was addressed as follows. First, the faecal prokaryotic community composition of horses suffering from FFW relative to healthy controls (n = 10) was compared. Second, FFW horses were treated with a standardised faecal microbiota transplantation (FMT) protocol (n = 10), followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…Furthermore, additional studies have also indicated the ineffectiveness of FMT in horses for the treatment of diarrhea. One particular study found no impact of FMT in addressing free fecal water in horses, suggesting that gut microbiota alterations may not be a contributing factor to this condition ( 20 ). Another study revealed that FMT achieved only a 67% success rate in managing diarrhea in a small cohort of six horses ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, additional studies have also indicated the ineffectiveness of FMT in horses for the treatment of diarrhea. One particular study found no impact of FMT in addressing free fecal water in horses, suggesting that gut microbiota alterations may not be a contributing factor to this condition ( 20 ). Another study revealed that FMT achieved only a 67% success rate in managing diarrhea in a small cohort of six horses ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no long-term evaluation was performed, and the recipient group was small and heterogenous (age differences, clinical signs and treatment) [ 106 ]. Laustsen et al treated ten horses suffering from Free Fecal Water syndrome (a condition characterized by the presence of water along with well-formed fecal balls) with FMT for five days [ 176 ]. No significant changes were found in the microbiota of the treated animals but, again, only 500 g of feces were used to prepare the FMT solution.…”
Section: Techniques Of Microbiota Manipulationmentioning
confidence: 99%
“…Also, there is no guarantee that FMT can treat all gastrointestinal disorders. A recent study documented a temporary effect worked when horses with Fecal Water Syndrome were treated with FMT [96]. However, it should be noticed that the main purpose of FMT is to restore a disrupted gut microbiota.…”
Section: Risks and Limits Of Equine Fecal Microbiota Transplantationmentioning
confidence: 99%